(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper provides brief overview of the river basin district management plans in the Baltic region within the WATERPRAXIS project, linked to the EU Water Framework Directive. Latvian experience in completion of the river basin district management plans is emphasized comparing to other regional cooperation partners. Article is based on the report documents, analysis of the available data and review of the development projects subject to implementation. To some extent also potential issues for discussion are outlined. Certain Baltic countries have had difficulties complying with the EU Water Framework Directive,and there are some potential areas of contention, which should be taken into account in further activities. In course of the administrative and territorial reform and compliance with other EU directives (e.g. in the renewable energy sector) modifications can be made to the status of spatial and also river basin management plans and for the purpose of sustainable development in the region.